MEASURING THE ROLE OF FAMILY FUNCTION IN PROMOTING ADOLESCENT REPRODUCTIVE HEALTH IN EAST JAVA - Irza Khurun'in; Iswari Hariastuti; Siswidiyanto Siswidiyanto; Sujarwoto Sujawoto (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2023)
A family function has a critical role in adolescent development especially in socializing healthy sexual behavior. However, studies around family function and reproduction health of adolescents are still limited. This research analyzes the link between family function on knowledge, attitude, and healthy sexual behavior among adolescents in East Java Province. Generalized Structural Equation Modelling (GSEM) was applied to the 2019 Performance and Accountability Survey (SKAP) 2019 East Java Province which consists of 32,194 families and 5,300 adolescents aged 10-24 years old. The results show that family functions are not well established, adolescents' knowledge of reproductive health is still low, and most adolescents have a negative attitude toward various population issues. The ability of families to socialize the five family function values is related to adolescent knowledge of reproductive health, positive attitudes toward population issues, and healthy reproductive behavior. This study suggests the importance of strengthening family functions to establish healthy reproductive behavior among adolescents in East Java.